Harnessing YouTube and Interactive Boards for Advancing Arabic Listening Competence - Moch. As’ad ihsan; Ainun Syarifah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to describe the use of YouTube-based interactive board media in supporting the development of listening skills (Maharah Istima’) among Grade VII F students at MTsN 1 Lamongan. Using a descriptive qualitative approach, this research involved the Arabic teacher and six students as key informants. Data were obtained through observation, interviews, and documentation collected on February 24, 2025. The findings show that the interactive board was utilized to display Arabic learning videos from YouTube, featuring native speaker pronunciation, simple dialogues, and contextual visuals. This combination of audio and visual elements helped students better understand vocabulary, pronunciation, and meaning. Students showed increased focus, enthusiasm, and participation during the learning process. However, several challenges were identified, including unstable internet connectivity and limited mastery of the interactive board’s advanced features. Overall, the use of YouTube-based interactive board media created a more engaging, contextual, and student-centered learning environment. This media supports students’ comprehension of spoken Arabic and aligns with the digital learning characteristics of today’s learners.